2016
DOI: 10.1111/hdi.12509
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the contact‐activation of coagulation during hemodialysis with three different polysulfone filters: A prospective randomized cross‐over trial

Abstract: The contact activation of coagulation during HD may also vary among filters made up with similar polysulfones. D-dimer in the filter rinsing fluid but not in the blood can be considered a candidate marker for the evaluation of thrombogenicity during HD. Further studies are needed to elucidate the mechanism(s) and to confirm the usefulness of filter rinsing fluid D-Dimers as a clotting activation marker during HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(64 reference statements)
2
2
0
Order By: Relevance
“…There was no difference in small solute, urea clearances when using the two dialyzers, and no difference in convective exchange. We found that D-dimers increased in the dialyzer outlet samples with both dialyzers, in keeping with previous reports using PS dialyzers, 23 but there was no significant increase in TATs post-dialyzer or increase with treatment duration. This small difference may potentially be due to the higher sieving coefficient and larger membrane surface area, although as we only made blood side measurements cannot exclude any membrane adsorption.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There was no difference in small solute, urea clearances when using the two dialyzers, and no difference in convective exchange. We found that D-dimers increased in the dialyzer outlet samples with both dialyzers, in keeping with previous reports using PS dialyzers, 23 but there was no significant increase in TATs post-dialyzer or increase with treatment duration. This small difference may potentially be due to the higher sieving coefficient and larger membrane surface area, although as we only made blood side measurements cannot exclude any membrane adsorption.…”
Section: Discussionsupporting
confidence: 92%
“…To study whether these changes in clotting cascade proteins lead to clot formation, we measured D-dimers and TATs. We found that D-dimers increased in the dialyzer outlet samples with both dialyzers, in keeping with previous reports using PS dialyzers, 23 but there was no significant increase in TATs post-dialyzer or increase with treatment duration. These results demonstrate that clot formation was minimal, as earlier studies have reported increased TATs within minutes of starting hemodialysis.…”
Section: Discussionsupporting
confidence: 92%
“…In the first one, comparing the same two membranes, we demonstrated, by measuring higher D-dimer levels in the dialyzer rinsing fluid, that the contact activation of coagulation during HD was more pronounced for Filter A in comparison with Filter B. 24 Even though it is not possible to draw conclusions, we can speculate that these findings might be related. Furthermore, interactions between coagulation and complement systems were extensively analyzed, and the involvement of the PSf HD membranes in complement pathway was demonstrated in proteomic studies on protein adsorption pattern performed with biomaterials used for HD membranes.…”
Section: Discussionmentioning
confidence: 87%
“…Others are assessed offline, such as visual 6 10 or software assisted 7 dialyzer redness scoring. Also laboratory parameters representing coagulation activity in general 6 8 , 11 13 , measured solute clearance 6 , 14 , evaluation of rinse-back 3 or fiber bundle volumes 15 17 and electron microscopy 9 have been used. None of these parameters is robust, objective or accurate, which limits the comparative study of different strategies to reduce coagulation and fiber blocking.…”
Section: Introductionmentioning
confidence: 99%